Rancangan Sistem Monitoring Bimbingan Laporan Kuliah Kerja Nyata (KKN) Universitas Harapan Medan Menggunakan V-Model - Nurdin, Ma'rifan; Sembiring, Boni Oktaviana; Nurjamiyah, Nurjamiyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
One of the tasks LPPM Universitas Harapan Medan is to accommodate and monitor activities of the Real Work Lecture reports for groups of students who have carried out RWL activities. Groups of students who are/have implemented services learning activities required to make a report done per group. In the reporting process, each group is required to conduct the counseling process RWL report to the Field Supervisor, which has been designated by the LPPM and Study Programs. The process of guiding the RWL report cannot run smoothly and on time if the busy schedule between lecturers and students does not match the time to meet, so this obstacle can make the problems that exist in writing reports cannot be solved as soon as possible. In this study, researchers have developed a system by applying the Model-V process. The V-model is an extension of the Waterfall model because the stages of development are the same, which distinguishing the Waterfall model in a linear manner. This study aims to build RWL report monitoring application by implementing a V-model based on a web service. For business processes the system uses UML. The results of the study make it easier for LPPM, RWL Student groups and Field Supervisors to carry out the process of guiding the RWL report.